Implementation of nagari expansion policy in Nagari Preparation for Koto Gadang Jaya, Kinali District, West Pasaman Regency - Annisa Hanif; Dimas Subekti (Masyarakat, Kebudayaan dan Politik, 2021)
The regional government of the West Pasaman Regency has implemented the nagari arrangement using the expansion of nagari. However, there are problems regarding the policy of nagari expansion in the Nagari Preparation of Koto Gadang Jaya. Therefore, this study aims to determine the strategies and problems of expanding the preparatory nagari in Koto Gadang Jaya, West Pasaman Regency. This research is qualitative research using a descriptive approach. Data collection techniques used interviews and documentation. This study used Edward III theory with communication variables, resources, dispositions, and bureaucratic structures. The research findings showed several problems related to implementing the expansion policy of the Nagari Preparation Koto Gadang Jaya; first, on communication variables in the indicators of transmission, clarity, and consistency; second, on the resource variable in human resources, financial resources, and infrastructure facilities indicators; third, the bureaucratic structure variable in the standard operating procedure indicators and fragmentation. Meanwhile, the excellent variable is disposition. This research concluded that the implementation of the policy of expanding the Nagari Preparation Koto Gadang Jaya has not been going well; several problems must be resolved by the party responsible for the policy.